Effect Of Preventive exercises on the of weights in the development of muscle strength of the arm used for badminton. - Dr. Muthana Ahmed Khalaf Omer Dhiab Mnaour (الرياضة المعاصرة)
The importance of the research in the preparation of exercises for the use of weights to develop the muscle strength of the arm used as a basis to prevent some of the injuries common to the players at the beginning of their career to avoid what happens with players infected in the advanced age, where the problem of research that the number of injuries in the arm used for the badminton The plane, especially the advanced players during training or competitions, is constantly increasing. These injuries are concentrated in three main joints (shoulder, elbow, wrist). The researcher therefore decided to highlight this problem in how to reduce these injuries and the possibility of The study aimed to prepare special exercises for the development of the muscle strength of the arm used as a basis for the prevention of some common injuries to badminton makers. The researcher used the experimental method and the design of the control and experimental groups with The experiment was chosen by the intentional way of the emerging players who represent the Baba Karkar Sports Club in Kirkuk Governorate.